V.I. Lenin (on the left) and L.D. Trockij on the Red Square during the celebration of the second anniversary of the Russian Revolution. Compare: 69/39, A, page 212 - Alekseev, N.,
V.I. Lenin (on the left) and L.D. Trockij on the Red Square during the celebration of the second anniversary of the Russian Revolution. Compare: 69/39, A, page 212.